The Influence of Interpersonal Communication and the Work Environmenton Member Commitment: Work Competency as the Mediating Variable - Ariestyawati, Siska (Economic Education Analysis Journal, 2024)
This research aims to analyze the influence of interpersonal communication and the work environment on member commitment through work competency as a mediating variable. The research uses a quantitative research approach. The research method is seen from data collection techniques using survey research methods. The population of the study was 53 members of the ICT division of the Central Java Regional Police, and the population was the sample. Data was collected using a questionnaire with a Likert scale. The questionnaire's statements were checked its validity and reliability. The data were then analyzed by the descriptive analysis and quantitative analysis. For quantitative analysis, this research uses data analysis using Smart-PLS software. The research results show that (1) interpersonal communication has a positive and significant effect on work competency; (2) the work environment has a positive and significant effect on work competency; (3) interpersonal communication has a positive and significant effect on member commitment; (4) the work environment has a positive effect on member commitment; (5) work competency has a positive and significant effect on member commitment; (6) work competency has no mediating role in the influence of interpersonal communication on member commitment; and (7) work competency has a partial mediating role in the influence of the work environment on member commitment.